Howes’ Analysis Measurement of Rumah Sakit Gigi dan Mulut Maranatha Bandung Patients - Evelyn Eunike (Journal of Medicine and Health, 2017)
Howes’ Analysis is an important tool in orthodontic treatment,as it can analyze abnormalities of teeth and jaw, to help diagnose and plan dental care. The aim of this study was to compare the length and width of the dental arch and the the apical base patients of Maranatha Dental and Mouth Hospital (Rumah Sakit Gigi dan Mulut Maranatha) / RSGM and Howes Analysis standard of Caucasian Race which considered to be the reference in determining of orthodontic treatment plan. The subjects consisted of 30 patients who met the inclusion criteria and the results data were analyzed by unpaired t test. The measured variable is the length of the dental arch, the width of the dental arch, and the width of the apical base, and calculated into Howes’ Index. The results showed that there were significant differences in the measurement of the length and width of the dental arch and the Howes Index; whereas the measurement of the apical base there was no significant difference between the results of the study and the reference of Caucasian Race. Conclusion, the length and width of the dental arch and the Howes’ Index did not differ between RSGM Bandung patients with Caucasian race standards whereas the apical base width was different.Keywords: Caucasian people, Howes’ analysis, Howes’ index, Maranatha Dental and Mouth Hospital Bandung